2006
DOI: 10.1007/s10549-006-9183-2
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 expression correlates with lymphovascular invasion and long-term prognosis in breast cancer

Abstract: Alterations in the mechanisms of apoptosis are responsible not only for the progression of breast cancer, but for different responses to treatment as well. Among the genes regulators of apoptosis, the tumor suppressor gene p53 and the bcl-2 gene have raised interest for their possible role as predictors of response to therapy and markers of prognosis. The purpose of our study was to prospectively analyze the prognostic value of the expression of p53 and bcl-2 genes in a series of 235 consecutive patients opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 29 publications
7
22
0
Order By: Relevance
“…In this study, Bcl-2 was more frequently associated with negative nodal status (100%) in both TNBC and non-TNBC and there was a significant inverse correlation with nodal positivity in non-TNBC group. This is consistent with the results obtained previously (Park et al, 2002;Neri et al, 2006), which indicate that the expression of Bcl-2 is a marker of breast cancer with reduced capability of distant colonization even in presence of lymphovascular invasion (Neri et al, 2006). On the contrary, Nadler et al (2008), found no association between expression of Bcl-2 and nodal status and Dawson et al (2010), verified the prognostic impact of Bcl-2 positivity regardless of lymph node status.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, Bcl-2 was more frequently associated with negative nodal status (100%) in both TNBC and non-TNBC and there was a significant inverse correlation with nodal positivity in non-TNBC group. This is consistent with the results obtained previously (Park et al, 2002;Neri et al, 2006), which indicate that the expression of Bcl-2 is a marker of breast cancer with reduced capability of distant colonization even in presence of lymphovascular invasion (Neri et al, 2006). On the contrary, Nadler et al (2008), found no association between expression of Bcl-2 and nodal status and Dawson et al (2010), verified the prognostic impact of Bcl-2 positivity regardless of lymph node status.…”
Section: Discussionsupporting
confidence: 91%
“…In our breast cancer material, Bcl-2 positivity was significantly lower in the early metastasizing group than in the latest metastasizing group, which is opposite to the results with cytoplasmic maspin and p53. A favorable outcome in Bcl-2-positive breast cancer has been reported in numerous studies [34][35][36]. Also in our study, the expression of Bcl-2 was significantly higher in the primary tumors than in the metastases in the early relapsing group.…”
Section: Discussionsupporting
confidence: 82%
“…In this regard, our results are in contrast with studies that suggest that bcl-2 expression is a favourable prognostic factor when primary surgical therapy is used. In other studies bcl-2 expression has been found to be an independent predictor of prognosis (7,8,12,10,18,38). However, other studies have shown opposite results (6,25,35,36,47).…”
Section: Discussionmentioning
confidence: 89%